Evolution of humic substances and the forms of heavy metals during co-composting of rice straw and sediment with the aid of Fenton-like process. (August 2021) - Chen, Yanrong; Chen, Yaoning; Li, Yuanping; Liu, Yihuan; Li, Hui; Jiang, Hongjuan; Luo, Xinli; Tang, Ping; Chen, Li; Yan, Haoqin
Graphical abstract: Highlights: Fenton-like process has been successfully applied to compost of agricultural waste. Fenton-like process could promote the generation of humic acid. Fenton-like process could improve the remediation of Cd and Cu. The stability of humic substances structure was enhanced. The effect of humus substance on the bioavailability of heavy metals was enhanced. Abstract: The Fenton-like process was established by Fe3 O4 nanomaterials (NMs) and Phanerochaete chrysosporium or oxalate, and applied to the co-composting of rice straw and sediment to study its effect on the formation of humic substance and the bioavailability of Cd, Cu, and Pb. Results shown that the application of Fenton-like process significantly promoted the passivation of Cd and Cu, while not shown obvious enhancement for Pb. The decrease of exchangeable fraction Cd (EXC-Cd) and the humic acid (HA) content in pile B with Fe3 O4 NMs and oxalate were highest, which were 22.35% and 20.3 g/kg, respectively. Redundancy analyses (RDA) manifested that the Fenton-like process enhanced the influence of humus substance on the bioavailability of Cd, Cu, and Pb. Excitation-emission matrix (EEM) fluorescence spectra analysis suggested that Fenton-like process could obviously enhance the generation of humic substance. This research provides a new perspective and way for composting to remediate heavy metals pollution.